Prevalence and determinants of spacing contraceptive use among rural married women of Jammu, India - Priyanka Khuda; Nand Lal Gupta; Nishikanth Palaka; Gurjeet Kaur (Wolters Kluwer Medknow Publications, 2021)
Introduction: Promotion of family planning, especially the use of contraceptive methods is essential to secure the well-being and development of society. Despite rise in the temporary contraceptive usage over the years, the implementation of the spacing method has been indicated lower in rural as compared to the urban areas of India. This study aims to find out the prevalence and determinants of current use of spacing contraceptives among married rural women of Jammu district, Jammu and Kashmir. Material and Methods: A community-based, cross-sectional study was conducted from January to June 2018 among married rural women. The survey was conducted house to house, and data were collected with the help of a questionnaire and BG Prasad Scale. Multi-stage sampling procedure was adopted to select the participants. Bivariate and multivariable logistic regression model was fitted to identify the factors associated with the current use of spacing contraceptive methods. Results: The current use of spacing contraceptive among married women was found to be 16.4%. The male condom was the most used method (55.7%) as well as most preferred contraceptive (46.8%). Lack of knowledge was reported as the main reason for not using contraceptive method. The current use of spacing contraceptive method was significantly higher among the upper socioeconomic status (adjusted odds ratio (AOR) 2.37(1.06-5.29), women with higher education (AOR ) 5.04 (0.68-37.18), living in nuclear family (AOR 1.90; CI: 1.01-3.60), with 2 or more surviving children (AOR ) 2.45 (1.27-4.73), and living near health center (AOR) 1.69 (0.91-3.14). Conclusion: Effective targeted programs along with conduction of more field researches that give scientific information should be implemented to achieve the desired goal of contraceptive usage in the rural area among married couples.